2010
DOI: 10.1002/clc.20581
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinical Trial Participation on Subsequent Antithrombin Use

Abstract: BackgroundResults from the Superior Yield of the New Strategy of Enoxaparin, Revascularization, and Glycoprotein IIb/IIIa Inhibitors (SYNERGY) trial showed that the low‐molecular‐weight heparin (LMWH) enoxaparin was non‐inferior compared with unfractionated heparin (UFH) in patients with non‐ST‐elevation acute coronary syndromes (NSTE‐ACS) managed invasively.HypothesisWe explored the influence of SYNERGY trial site participation on subsequent patterns of heparin use for NSTE‐ACS patients treated in routine pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…Two studies in the field of cardiovascular research were unable to find an effect of recruitment for a clinical trial on the implementation rate of the trial results [12,13]. This might be explained by the fact that the clinicians were not convinced by the results of a single trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in the field of cardiovascular research were unable to find an effect of recruitment for a clinical trial on the implementation rate of the trial results [12,13]. This might be explained by the fact that the clinicians were not convinced by the results of a single trial.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ketley and Woods [11] in 1993 has shown that the level of use of thrombolytic drugs was strongly associated with the extent of involvement in multicenter trials of thrombolysis: 64% of the variation in thrombolytic use between districts in that year could be accounted for by districts' participation in multicenter trials during the preceding 2 years (p = 0.003). Shah et al [12] studied the influence of participation of sites in the Superior Yield of the New Strategy of Enoxaparin, Revascularization and Glycoprotein IIb/IIIa Inhibitors (SYNERGY) trial on the type of heparin subsequently used; site participation did not alter patterns of low-molecular-weight heparin use for non-ST-elevation acute coronary syndromes after publication of the trial results.…”
Section: Introductionmentioning
confidence: 99%
“…The literature to date has not demonstrated a link between participation in research and subsequent knowledge use, and no research on this topic has been conducted in Australia or NZ or in ICU. Some studies reported no increased knowledge or use of results, despite personal or institutional involvement in a clinical trial even when the RCT showed very high quality evidence (Khera et al, 2018;Majumdar et al, 2002;Shah et al, 2010), while other studies showed mixed results (Kizer et al, 1999;Litjens et al, 2013;Sweeting et al, 2020).…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…interventions that can easily be studied. Included in this category are multiple studies about whether doctors' participation in a drug trial changed their prescribing that drug, by reviewing prescription records (Corrigan & Glass, 2005;Ketley & Woods, 1993;Majumdar et al, 2002;Shah et al, 2010). A few studies of this nature emerged in the late 1990s and early 2000s, possibly related to the increasing evidence about drugs to successfully manage cardiac disease.…”
Section: Overview Of Literaturementioning
confidence: 99%
See 1 more Smart Citation